ETHICS OF AI USE IN MARKETING COMMUNICATIONS: CHALLENGES AND SOLUTIONS - Gina Valerina; Leonardus Wahono Kurniawan; Veronica Nurma (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to analyze the ethical challenges in the use of Artificial Intelligence (AI) in marketing communications and identify applicable solutions to address these issues. AI has provided significant benefits in marketing, particularly in terms of personalization, automation, and operational efficiency. However, challenges related to data privacy, algorithmic bias, and a lack of transparency in AI use raise significant ethical concerns. This study uses a qualitative approach with literature analysis and in-depth interviews to explore the implementation of AI in various companies. The results indicate that transparency in AI use, responsible data management, and regular algorithm audits are important solutions to maintain ethics in AI-based marketing communications. The conclusion of this study is that although AI offers significant opportunities to improve marketing effectiveness, marketers must be careful in handling ethical aspects to maintain consumer trust and avoid negative impacts.